The happiness of sharing chocolate in the classroom (Journal of Parents and Teachers, 2013)
The author presents his project in which he pretends to review several contents at the end of the school year, with pupils of fifth year of primary education and based on chocolate. The author explains the curricular planning the development activities for a week and the evaluation.
Keywords: Primary education; pilot project; didactics; chocolate; education.